The effect of different etiologies of hepatic impairment on the pharmacokinetics of gefitinib. - Horak, J; White, J; Harris, A; Verrill, M; Carmichael, J; Holt, A; Cantarini, M; Macpherson, M; Swaisland, A; Swaisland, H; Twelves, C (2011)
PURPOSE: We investigated whether the pharmacokinetics and tolerability of gefitinib were altered in patients with hepatic impairment due to cirrhosis or hepatic metastases in two open, parallel-group, multicenter studies. METHODS: In Study 1, subjects with normal hepatic function or mild, moderate, or severe hepatic impairment (Child-Pugh criteria) due to cirrhosis received single-dose gefitinib 250 mg (n = 10 per group). In Study 2, patients with solid malignant tumors with normal liver biochemistry (n = 18), moderate (n = 16), or severe (n = 7) hepatic impairment (liver biochemistry tests) due to metastases received gefitinib 250 mg daily for 28 days. RESULTS: In Study 1, the geometric mean area under the plasma concentration-time curve (AUC) for gefitinib was significantly higher in patients with hepatic impairment compared with healthy subjects; hepatic impairment was associated with reduced gefitinib plasma clearance, longer half-life, and reduced plasma metabolite levels. In Study 2, the geometric mean gefitinib steady-state AUC during the 24-h dosing interval was slightly, but not significantly, higher in patients with moderate hepatic impairment; there were, however, no significant differences between groups in gefitinib and metabolite pharmacokinetic parameters. In both studies, gefitinib was well tolerated across all cohorts. CONCLUSIONS: We conclude that the effect of hepatic impairment on gefitinib pharmacokinetics depends on the underlying etiology of that impairment and its classification.